Adsorption of tetracycline in water by Fe³⁺ functionalized carboxymethyl chitosan aerogel - Abad, Ignacio; Leibfarth, Logan (Journal of Green Energy and Environmental Engineering, 2026)
Using carboxymethyl chitosan (CMCS) as raw material, Fe³⁺-initiated gelation successfully produced a novel CMCS@Fe³⁺ composite aerogel for tetracycline (TC) adsorption. The study demonstrates that this composite exhibits outstanding adsorption performance for TC. At 298 K, the maximum adsorption capacity fitted by the Sips model isotherm is as high as 785.85 mg/g, significantly exceeding most previously reported data. Material characterization, density functional theory (DFT) calculations, and material ratio experiments revealed synergistic effects between CMCS and Fe³⁺ during adsorption. Hydrogen bonding and Fe³⁺ coordination were identified as key adsorption mechanisms, with Fe³⁺ coordination playing a central role. Furthermore, this adsorbent demonstrated stable performance in cyclic adsorption experiments, achieving satisfactory adsorption results even under varying inorganic salt concentrations and simulated aquaculture wastewater treatment scenarios. In summary, CMCS@Fe³⁺ exhibits significant application potential for tetracycline removal from water.